Prospective Clinical Trial of the Oncologic Outcomes and Safety of Extraperitoneal Laparoscopic Extended Retroperitoneal Lymph Node Dissection at Time of Nephroureterectomy for Upper Tract Urothelial Carcinoma - Huang, Jiwei; Qian, Hongyang; Yuan, Yichu; Cai, Xingyun; Chen, Yonghui; Zhang, Jin; Kong, Wen; Wu, Xiaorong; Cao, Ming; Huang, Yiran; Chen, Haige; Xue, Wei (Frontiers in Oncology, 2022)
Purpose To determine the safety and feasibility of extraperitoneal laparoscopic extended lymph node dissection (LND) at the time of extraperitoneal laparoscopic radical nephroureterectomy (RNU). Materials and Methods Between May 2018 and March 2019, 39 patients with upper tract urothelial carcinoma (UTUC) received extraperitoneal laparoscopic RNU and concomitant extraperitoneal laparoscopic extended LND. All patients were followed for at least 90 days. Perioperative and pathological data including nodal status and perioperative complications were collected. Results Among all 39 patients, 12 patients had pT1, 6 had pT2, 20 had pT3 disease, and 1 had T4 disease. The median (range) lymph node count was 10 (5–22), with 8 patients having pathologically proven lymph node metastasis. The median (range) operating time was 225 (165–430) min, and the median estimated blood loss was 200 (60–800) ml. The median postoperative hemoglobin loss was 1.6 (0–4.2) g/dl. The median (range) postoperative hospital stays were 6 (3–26) days. Overall, 7 patients experienced minor (Clavien Grade I–II) postoperative complications with five patients having Clavien Grade I complications and two patients having Clavien Grade II complications. No major complication (Clavien grade III–IV) occurred. With a median follow-up of 38 months, a total of 8 patients (20.5%) developed local or distant recurrence and no regional LNs where extended LND were performed had recurrence. Conclusions The present prospective study demonstrated that extraperitoneal laparoscopic extended LND during extraperitoneal laparoscopic RNU for UTUC is a feasible and safe procedure which provides minimal invasion, rapid recovery, and potentially lower risk of regional LN recurrence. Larger prospective clinical trials with survival endpoints are needed to further determine its potential therapeutic benefits. Trial Registration ClinicalTrials.gov identifier NCT 03544437 www.clinicaltrials.gov